Seed Treatment with Pesticide, Bordeaux Mixture and Biological Agent for Ginger Rhizome-Borne Disease Suppression - Djiwanti, Setyowati Retno; Sri Rahayuningsih (Jurnal Fitopatologi Indonesia, 2022)
Seed Treatment with Pesticide, Bordeaux Mixture and Biological Agent for Ginger Rhizome-Borne Disease Suppression Root knot caused by nematodes and rhizome rot due to infection by various pathogens is commonly found in ginger rhizomes. A study was conducted to evaluate the effect of several seed treatments on suppression of rhizome damage caused by these diseases. The experiment was arranged using a randomized block design with 7 rhizome treatments, each repeated 4 times. Ginger rhizome were given treatment before planting, i.e. soaking in 1.5% pesticides (a mixture of streptomycin sulfate and benomyl), Bordeaux mixture (1% and 2%), 10% rhizobacteria (Bacillus pantotkenticus and Trichoderma lactae) for 24 hours; and coating with carbosulfan ST flour (500 g for 4 kg rhizomes) and non-pathogenic Fusarium (NP) talc formula (500 g for 4 kg rhizomes). Ginger rhizomes were than planted in sterile planting medium consisting of a mixture of 1% Bordeaux mixture and soil; and observed until the plants reach 5 months old. Soaking the rhizomes in a solution of pesticides and rhizobacterial formulas, as well as coating the rhizomes with carbosulfan ST flour and Fusarium NP formulas could suppress root knot and rhizome rot; Those seed treatments also enhanced seed viability and plant growth (plant fresh weight and or rhizome dry weight). With the exception of Bordeaux mixture, these four seed treatments can be further used in the production of qualified and healthy ginger rhizome seed.